Bovine anaplasmosis in Turkey: First laboratory confirmed clinical cases caused by Anaplasma phagocytophilum - Aktas M, Özübek S. (My University, 2015)
Anaplasma species are obligate intracellular rickettsial pathogens that affect the health of humans and other animals. Clinical cases of anaplasmosis caused by Anaplasma phagocytophilum were evaluated, and the frequency of bovine Anaplasma species was determined in cattle. Blood samples and thin blood smears were collected from 10 cattle exhibiting clinical signs of tick-borne fever. In addition, blood samples were collected from 123 apparently healthy cattle from the same area. DNA was screened by reverse line blot assay for the presence of the hypervariable V1 region of the 16S rRNA gene of Anaplasma/ Ehrlichia species. Intracytoplasmic inclusion bodies of A. phagocytophilum were observed in neutrophils of 6 sick animals. Parasitemia ranged from 0.2 to 1.6% in individual slides. Reverse line blot showed 45.1% (60/133) of the sampled cattle to be positive for one or more of five Anaplasma species. The frequency of single infections was 20.3% (27/133), while mixed infections were found in 24.8% (33/133) of samples with six different combinations of species and a maximum of four pathogens detected. A. phagocytophilum was the most prevalent (41/133, 30.8%) followed by Anaplasma marginale (25/133, 18.8%), Anaplasma centrale (24/133, 18%), Ehrlichia sp. strain Omatjenne (18/133, 13.5%) and Anaplasma bovis (1/133, 0.7%). This is the first report of A. bovis in a cow from Turkey. This is also the first report of clinical cases caused by A. phagocytophilum in cattle from the country. Therefore, A. phagocytophilum should be taken into account as differential diagnosis in cases of high fever and anorexia in pastured animals.
Sığır Anaplasmosisi
Makale - Yabancı Dilde Makale
Keywords: Tick-borne fever; RLB; Anaplasma phagocytophilum